Issues in intimate violence - Bergen, Raquel Kennedy (SAGE, 1998)
This volume provides the basis for understanding a wide range of interpersonal violence: child abuse; incest; violence in heterosexual, gay and lesbian relationships; acquaintance rape; wife abuse and rape; and elder abuse. There is no single accepted explanation for interpersonal violence, and the chapters reflect this by representing a number of disciplines from both theoretical and applied viewpoints. Many chapters take a feminist perspective, addressing the gendered nature of violence.